(untitled) (Sociologisk Forskning, 2018)
Radical right online discussion groups have grown in importance in the Swedish political landscape, yet the dynamics of these groups are still poorly understood. Apart from their topical import, these groups provide a unique entrance to grassroots discourses of the radical right movement and the mechanisms for radical nationalist mobilization. In this paper, we present an analysis of the largest current anti-immigrant online discussion group in Sweden by using a combination of quantitative and qualitative content analysis. We argue that this type of social media group needs to be approached as both a “counterpublic” within a wider public sphere and as a “free social space” for social movements. The analysis reveals that the use of external links in the group reflects an active negotiation of frames that both confirm and contradict those of the group, thereby challenging a simplistic understanding of the so-called “echo chamber” dynamics. A form of collective identity can be discerned, mainly through the opposition to various outgroups and through an implicit form of nationalism expressed through the concern of “sacred objects” typically perceived to be under threat.